Post-kinematic mafic dykes in southern part of Central Svecofennia, Finland - J. Kara; M. Väisänen; Y. Lahaye; H. O’Brien (Finland, 2025)
The geochemical composition of seven post-kinematic mafic dykes in southern part of Central Svecofennia have been studied. Two dykes have been selected for in situ zircon U-Pb geochronology and one for in situ zircon Lu-Hf isotope analysis.These c. 1.86 Ga dykes can be divided into two subgroups by their geochemical characteristics: i) an enriched type with Nb contents up to 42 ppm, high contents of certain fluid mobile elements such as F, Ba, Sr, K2O and LREE and elevated contents of Fe2O3, Ti2O and P2O5, and ii) a primitive type with high MgO and Cr content. The primitive dyke exhibit positive, average c. +3, initial εHf values. The geochemical data combined with the petrological and the field observations suggest that the dykes are juvenile and derived from a subduction-enriched mantle source in a within-plate environment during the post-kinematic stage of the Svecofennian orogeny.
Lithosphere 2016: Ninth symposium on the Structure, Composition and Evolution of the Lithosphere in Fennoscandia